Air hydrogen production material, preparation method and application
By using porous composite materials of graphene aerogel and MOF materials, the problems of high material cost, low catalytic efficiency and insufficient stability in the existing hydrogen production technology are solved, efficient and low-consumption hydrogen production is achieved, and the materials are improved chemical stability.
Patent Information
- Application Number
- CN202411449872.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
AI Technical Summary
The existing hydrogen production technology has high material costs, low catalytic efficiency and insufficient material stability, resulting in high energy consumption and poor economic benefits of hydrogen production.
Using a porous composite material of graphene aerogel and MOF materials, graphene is used to absorb solar energy and convert it into thermal energy, and MOF materials are used to absorb water vapor in the air and catalyze the production of hydrogen under sunlight.
It realizes efficient and low-cost production of hydrogen, improves catalytic efficiency, enhances the chemical stability of the material, reduces energy consumption, and the material can be regenerated under appropriate conditions, extends its service life.
Smart Images

Figure CN119390012A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogen production from air, and in particular to a hydrogen production material from air, a preparation method and an application thereof. Background Art
[0002] With economic development and population growth, the demand for energy continues to increase, and the environmental pollution and resource depletion caused by fossil fuels are becoming increasingly prominent. The United Nations Sustainable Development Goals (SDGs) emphasize the sustainable use of water resources and the development of clean energy to promote the sustainable development of human society. Hydrogen energy is a clean and efficient energy that only produces water when burned and has extremely high application potential. Hydrogen energy is widely studied by scholars as a clean energy that can power automobiles. Combining air water extraction technology with hydrogen production technology can achieve the acquisition of clean water from the air and convert it into hydrogen energy, thereby solving the problems of water shortage and energy crisis.
[0003] At present, hydrogen production technologies mainly include water electrolysis, coal gasification and biomass conversion, but these methods have significant limitations in terms of material costs. For example, water electrolysis requires high-performance electrode materials and catalysts, which are usually made of rare or precious metals such as platinum and iridium, which are expensive, resulting in high overall hydrogen production costs. Although coal gasification is a relatively mature technology, the catalysts and separation membranes required are often made of expensive materials, and when working under high temperature and high pressure conditions, the stability and life of these materials are key issues, further increasing the cost of material replacement and maintenance.
[0004] In the production of hydrogen from biomass, although the sources of raw materials are relatively wide, the processing process requires specific enzymes or catalysts. These key materials are also relatively expensive and are usually difficult to recycle and reuse. In addition, the complexity of hydrogen production equipment places higher demands on the performance and durability of materials, resulting in the need to give priority to high-cost materials when selecting materials to meet the long-term stable operation of the equipment. These high material costs not only increase the initial investment in the hydrogen production process, but also affect the subsequent economic benefits, becoming the main obstacle to large-scale and economical hydrogen production. Summary of the invention
[0005] The present invention provides an air hydrogen production material, a preparation method and an application, the purpose of which is to achieve stable production of hydrogen with high efficiency and low consumption, and to solve the problems of high energy consumption, low catalytic efficiency and insufficient material stability in hydrogen production in the prior art.
[0006] To achieve the above object, one of the technical solutions of the present invention is:
[0007] An air hydrogen production material comprises: graphene aerogel and MOF material, wherein the graphene aerogel can absorb solar energy and convert it into thermal energy, and the MOF material can adsorb water vapor in the air and catalyze a reaction to produce hydrogen under sunlight.
[0008] In some preferred embodiments, the MOF material is selected from one or more of MOF-303, CAU-10-H, Ni2Cl2(BTDD), and MOF-801.
[0009] In some preferred embodiments, the graphene aerogel and MOF material are combined to form a porous composite material through a polymer binder, and the polymer binder is selected from one or more of polyvinyl alcohol, sodium alginate, polyacrylamide or poly (N-isopropylacrylamide).
[0010] The weight ratio of the graphene aerogel to the MOF material is 4:1 to 20:1.
[0011] In some preferred embodiments, the graphene aerosol is a lamellar structure, with one or more of the sizes ranging from 200nm to 20μm.
[0012] The second technical solution of the present invention is:
[0013] The method for preparing the air hydrogen production material comprises the following steps:
[0014] 1) preparing a precursor solution comprising graphene oxide, a polymer binder and a MOF material as required;
[0015] 2) Freezing the precursor solution to form a solid composite;
[0016] 3) freeze-drying the solid composite in vacuum to obtain a porous composite material;
[0017] 4) Performing a reduction reaction on the porous composite material to form an air hydrogen production material.
[0018] In some preferred embodiments, the step 1) is specifically: using 0.5 mg / mL-20 mg / mL concentration of graphene, 0.1%-20% mass fraction of polymer binder, and MOF material in a mass ratio of 4::4:1-20:20:1 to stir and prepare a precursor solution, wherein the mass ratio of the graphene oxide to the polymer binder is 1:1-1:5.
[0019] In some preferred embodiments, the step 2) specifically includes: pouring the precursor solution A into a mold, and freezing it into a solid composite using liquid nitrogen or a temperature below -30°C.
[0020] In some preferred embodiments, the reduction reaction in step 4) is carried out at a temperature of 150° C.-500° C. for 2 hours.
[0021] The third technical solution of the present invention is:
[0022] The application of air hydrogen production materials in air hydrogen production is to adsorb water vapor from the air and catalytically produce hydrogen under light conditions.
[0023] The beneficial effects achieved by the present invention are:
[0024] On the one hand, graphene materials have high solar energy absorption performance and high photothermal conversion performance, which can effectively convert solar energy into thermal energy, thereby improving light absorption efficiency. On the other hand, MOF materials have high specific surface area and unique pore structure, which provides more active sites for catalysis and realizes in-situ water adsorption and hydrogen catalysis. Furthermore, through the unique freeze-drying design, the material forms a porous structure, which increases the specific surface area with air, thereby effectively reducing energy consumption.
[0025] In addition, graphene and MOF materials have excellent chemical stability, which can maintain good light absorption performance and catalytic activity during long-term use, reducing the attenuation of the catalyst. In the experiment, as the light intensity increases, the rate of hydrogen generation also increases. MOF materials absorb photon energy, causing electrons to jump from the valence band to the conduction band, generating electron-hole pairs, and the separated electrons are transferred to the active site and reduce the protons (H + ), generating hydrogen (H 2 At the same time, the holes participate in the oxidation reaction of water to generate oxygen (O2) and protons (H + ), maintaining the charge balance of the reaction. The greater the light intensity, the higher the catalytic efficiency. MOF materials with good lattice structure and abundant active sites can catalyze water splitting reactions more efficiently.
[0026] In addition, MOF materials can be regenerated by heating, decompression or chemical washing. MOF materials can effectively restore their adsorption properties under appropriate conditions. Graphene exhibits good corrosion resistance and durability, suitable for long-term use. Even if the material performance decays with changes in light, it can still maintain 96% of its performance after three years of use.
[0027] Furthermore, the materials of the present invention can work in different application scenarios, especially MOF materials can allow the liquid storage tank to work under a wider range of operating conditions, including different temperatures and humidity. Therefore, the material can adapt to different application scenarios, realize distributed hydrogen generation, and is suitable for efficient hydrogen production in a variety of environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a physical diagram of embodiment 6 of the present invention;
[0029] Figure 2 The sample of Example 6 (area 50cm 2 ), a graph showing the change in hydrogen production rate under sunlight on a certain day. DETAILED DESCRIPTION
[0030] An air hydrogen production material comprises: graphene aerogel and MOF material, wherein the graphene aerogel can absorb solar energy and convert it into thermal energy, and the MOF material can adsorb water vapor in the air and catalyze a reaction to produce hydrogen under sunlight.
[0031] In some preferred embodiments, the MOF material is selected from one or more of MOF-303, CAU-10-H, Ni2Cl2(BTDD), and MOF-801.
[0032] In some preferred embodiments, the graphene aerogel and MOF material are combined to form a porous composite material through a polymer binder, and the polymer binder is selected from one or more of polyvinyl alcohol, sodium alginate, polyacrylamide or poly (N-isopropylacrylamide).
[0033] The weight ratio of the graphene aerogel to the MOF material is 4:1 to 20:1.
[0034] In some preferred embodiments, the graphene aerosol is a lamellar structure, with one or more of the sizes ranging from 200nm to 20μm.
[0035] The method for preparing the air hydrogen production material comprises the following steps:
[0036] 1) preparing a precursor solution comprising graphene oxide, a polymer binder and a MOF material as required;
[0037] 2) Freezing the precursor solution to form a solid composite;
[0038] 3) freeze-drying the solid composite in vacuum to obtain a porous composite material;
[0039] 4) Performing a reduction reaction on the porous composite material to form an air hydrogen production material.
[0040] In some preferred embodiments, the step 1) is specifically: using 0.5 mg / mL-20 mg / mL concentration of graphene, 0.1%-20% mass fraction of polymer binder, and MOF material in a mass ratio of 4::4:1-20:20:1 to stir and prepare a precursor solution, wherein the mass ratio of the graphene oxide to the polymer binder is 1:1-1:5.
[0041] In some preferred embodiments, the step 2) specifically includes: pouring the precursor solution A into a mold, and freezing it into a solid composite using liquid nitrogen or a temperature below -30°C.
[0042] In some preferred embodiments, the reduction reaction in step 4) is carried out at a temperature of 150° C.-500° C. for 2 hours.
[0043] The application of air hydrogen production materials in air hydrogen production is to adsorb water vapor from the air and catalytically produce hydrogen under light conditions.
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0046] There is no particular limitation on the purity of all raw materials in the present invention, and analytically pure or prepared raw materials are preferred.
[0047] All raw materials and process steps of the present invention, their brands or abbreviations are conventional brands or abbreviations in the art, and each brand or abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods, or implement them with corresponding equipment according to the brands, abbreviations and corresponding uses.
[0048] Embodiment 1:
[0049] A precursor solution was prepared by mixing 0.5 mg / mL of graphene oxide with a single sheet structure (sheet size of 500 nm) with 0.1% polyvinyl alcohol and MOF-303 in a mass ratio of 4:4:1, and stirred evenly with a porcelain stirrer and a homogenizer. The precursor solution was poured into a mold and frozen at -35°C to form a solid composite. The solid composite was then freeze-dried in a vacuum to obtain a porous composite material. Finally, the porous composite material was reduced at 150°C for 2 hours to prepare an air hydrogen production material.
[0050] Embodiment 2:
[0051] A precursor solution was prepared by mixing 0.5 mg / mL of single-sheet graphene oxide (sheet size of 200 nm) with 0.1% sodium alginate and Ni2Cl2 (BTDD) in a mass ratio of 4:4:1, and stirred evenly with a porcelain stirrer and a homogenizer. The precursor solution was poured into a mold and frozen at -40°C to form a solid composite. The solid composite was then freeze-dried in a vacuum to obtain a porous composite material. Finally, the porous composite material was reduced at 300°C for 2 hours to prepare an air hydrogen production material.
[0052] Embodiment 3:
[0053] A precursor solution was prepared by mixing 0.5 mg / mL of graphene oxide (lamellar structure, a mixture of 200 nm, 500 nm and 1 μm in molar ratio of 1:1:1) with a mixed polymer binder of 0.1% by mass and a single MOF material in a mass ratio of 4:4:1. The mixed polymer binder is polyvinyl alcohol and sodium alginate, mixed in a mass ratio of 1:1; the MOF material is MOF-303. The mixture was stirred evenly using a porcelain stirrer and a homogenizer. The precursor solution was poured into a mold and frozen at -50°C to form a solid composite. The solid composite was then freeze-dried in vacuum to obtain a porous composite material. Finally, the porous composite material was reduced at 400°C for 2 hours to prepare an air hydrogen production material.
[0054] Embodiment 4:
[0055] A precursor solution was prepared by mixing 0.5 mg / mL of graphene oxide (lamellar structure, a mixture of 200 nm, 500 nm and 1 μm in molar ratio of 1:1:1) with a single polymer binder of 0.1% by mass and a mixed MOF material of 4:4:1 by mass ratio. The polymer binder is polyacrylamide, and the MOF materials are MOF-801 and CAU-10-H, which are mixed in a mass ratio of 1:1. The mixture was stirred evenly with a porcelain stirrer and a homogenizer. The precursor solution was poured into a mold and frozen at -55°C to form a solid composite. The solid composite was then freeze-dried in vacuum to obtain a porous composite material. Finally, the porous composite material was reduced at 350°C for 2 hours to prepare an air hydrogen production material.
[0056] Embodiment 5:
[0057] A precursor solution is prepared by mixing 0.5 mg / mL of graphene oxide (lamellar structure, a mixture of 200 nm, 500 nm and 1 μm in molar ratio of 1:1:1) with 0.1% of a mixed polymer binder and a mixed MOF material in a mass ratio of 4:4:1. The mixed polymer binder is polyvinyl alcohol and polyacrylamide, mixed in a mass ratio of 1:1; the mixed MOF material is MOF-303 and Ni2Cl2 (BTDD), mixed in a mass ratio of 1:1. The mixture is stirred evenly with a porcelain stirrer and a homogenizer. The precursor solution is poured into a mold and frozen in an environment of -60°C to form a solid composite. The solid composite is then freeze-dried in vacuum to obtain a porous composite material. Finally, the porous composite material is reduced at 200°C for 2 hours to prepare an air hydrogen production material.
[0058] Example 6
[0059] A precursor solution was prepared by mixing 0.5 mg / mL of graphene oxide (lamellar structure, a mixture of 200 nm, 500 nm and 1 μm in molar ratio of 1:1:1) with a mixed polymer binder and a mixed MOF material at a mass ratio of 4:4:1 at a mass fraction of 0.1%. The mixed polymer binder is polyvinyl alcohol and poly (N-isopropylacrylamide), which are mixed at a mass ratio of 1:1; the mixed MOF material is MOF-801 and CAU-10-H, which are mixed at a mass ratio of 1:1. The mixture was stirred evenly with a porcelain stirrer and a homogenizer. The precursor solution was poured into a mold and frozen at -65°C to form a solid composite. The solid composite was then freeze-dried in vacuum to obtain a porous composite material. Finally, the porous composite material was reduced at 150°C for 2 hours to prepare an air hydrogen production material.
[0060] In the present invention, the abundant oxygen-containing functional groups on the graphene surface can provide a wide range of spatial locations for MOF to store water after adsorbing water vapor, thereby promoting continuous adsorption of MOF.
[0061] According to the test, the air hydrogen production material of the present invention has a good hydrogen production capacity under natural light. Figure 2 As shown in the figure, the hydrogen production rate of the material in Experiment 6 increases with the increase of light intensity. 2 ·h), the hydrogen production rate is 104ml / h. 3. Graphene has the function of absorbing solar energy and converting light energy into heat energy, while MOF mainly has the function of catalyzing hydrogen.
[0062] When MOF materials are exposed to light, the organic linkers or metal nodes in the material absorb the photon energy, causing electrons to jump from the valence band to the conduction band, generating electron-hole pairs. The separated electrons are transferred to the active sites of MOF, which are usually located on the metal nodes. The electrons can reduce the protons (H + ), generating hydrogen (H2). At the same time, the holes may participate in the oxidation reaction of water to generate oxygen (O2) and protons (H + ). This process helps maintain the charge balance of the reaction. The greater the light intensity, the higher the catalytic efficiency. MOFs with a good lattice structure can more effectively separate and transport electron-hole pairs, thereby improving catalytic efficiency. MOFs with rich and efficient active sites can more effectively catalyze water decomposition reactions. MOF materials can be achieved by heating, decompression or chemical washing. Most MOFs can be effectively regenerated under appropriate conditions to restore their adsorption properties. In most environments, graphene exhibits good corrosion resistance and durability and is suitable for long-term use. The material properties will decay slightly with changes in light exposure. 96% of the performance can be maintained for three years.
[0063] The above is a detailed description of the present invention, the purpose of which is to enable people familiar with the technology in this field to understand the content of the present invention and implement it, and it is not intended to limit the scope of protection of the present invention. The present invention is not limited to the above-mentioned embodiments. Any equivalent changes or modifications made according to the spirit of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A material for producing hydrogen from air, characterized in that: The invention comprises: graphene aerogel and MOF material, wherein the graphene aerogel can absorb solar energy and convert it into thermal energy, and the MOF material can absorb water vapor in the air and catalyze a reaction to produce hydrogen under sunlight.
2. The air hydrogen production material according to claim 1, characterized in that: The MOF material is selected from one or more of MOF-303, CAU-10-H, Ni2Cl2 (BTDD), and MOF-801.
3. The air hydrogen production material according to claim 1, characterized in that: The graphene aerogel and the MOF material are combined with a polymer binder to form a porous composite material, and the polymer binder is selected from one or more of polyvinyl alcohol, sodium alginate, polyacrylamide or poly (N-isopropylacrylamide).
4. The air hydrogen production material according to claim 1, characterized in that: The weight ratio of the graphene aerogel to the MOF material is 4:1 to 20:
1.
5. The air hydrogen production material according to claim 1, characterized in that: The graphene aerosol is a sheet structure, and adopts one or more of 200nm-20μm.
6. A method for preparing the air hydrogen production material according to claims 1-5, characterized in that: The following steps are involved: 1) preparing a precursor solution comprising graphene oxide, a polymer binder and a MOF material as required; 2) Freezing the precursor solution to form a solid composite; 3) freeze-drying the solid composite in vacuum to obtain a porous composite material; 4) Performing a reduction reaction on the porous composite material to form an air hydrogen production material.
7. The method for preparing a hydrogen production material from air according to claim 6, characterized in that: The step 1) is specifically as follows: graphene with a concentration of 0.5 mg / mL-20 mg / mL, a polymer binder with a mass fraction of 0.1%-20%, and MOF material are stirred in a mass ratio of 4::4:1-20:20:1 to form a precursor solution, wherein the mass ratio of the graphene oxide to the polymer binder is 1:1-1:
5.
8. The method for preparing a hydrogen production material from air according to claim 7, characterized in that: The step 2) is specifically as follows: pouring the precursor solution A into a mold, and freezing it into a solid composite using liquid nitrogen or a temperature below -30°C.
9. The method for preparing a hydrogen production material from air according to claim 6, characterized in that: The reduction reaction in step 4) is carried out at a temperature of 150° C. to 500° C. for 2 hours.
10. The use of the air hydrogen production material according to any one of claims 1 to 9, characterized in that: The air hydrogen production material is used for absorbing water vapor from the air and catalytically producing hydrogen under light conditions.
Citation Information
Cited By
Preparation method and application of Ce (OTf) 3-MOF-303-coated GO composite adsorption material
CN121288789A